"Essential Collaborators": Locating Middle Eastern Geneticists in the Global Scientific Infrastructure, 1950s–1970s. (January 2018) - Burton, Elise K.
Abstract: In the aftermath of World War II, a new international infrastructure based on United Nations agencies took charge of coordinating global biomedical research. Through this infrastructure, European and American geneticists hoped to collect and test blood samples from human populations across the world to understand processes of human heredity and evolution and trace the historical migrations of different groups. They relied heavily on local scientific workers to help them identify and access populations of interest, although they did not always acknowledge the critical role non-Western collaborators played in their studies. Using scientific publications, personal correspondence, and oral histories, I investigate the collaborative relationships between Western scientists, their counterparts in the Middle East, and the human subjects of genetic research. I comparatively examine the experiences of Israeli and Iranian scientists and physicians engaged in genetic anthropology and medical genetics between the mid-1950s and the late 1970s, noting how they both applied nationalist historical narratives to their genetic data and struggled to establish the value of their local knowledge and scientific labor. I argue that the Israeli and Iranian experience of transnational scientific collaboration is representative of how Western scientists relegated their collaborators from "developing" regions to a subordinate positionality as collection agents or native informants. Meanwhile, within their own countries, the elite professional identity of Israeli and Iranian scientists granted them the authority to manipulate their research subjects, who often belonged to marginalized minority communities, and to interpret their biology and history within contexts of Jewish and Persian nationalism.